PARTISIPASI MASYARAKAT PADA PROGRAM POS PELAYANAN TERPADU (POSYANDU) DI DESA WAITINA KECAMATAN MANGOLI TIMUR - Umasangaji, M. Isnain (Universitas Sam Ratulangi, 2016)
The problems were found in the Waitina village have a research concerning with public participation in the Pos Pelayanan Terpadu (posyandu) that is the facilities required by health workers so that the service less so fulfilling for the more especially for toddlers and pregnant mothers. Program that should run well or effective finally not in accordance with what is expected, and communities still have not too knowing benefit and importance of posyandu for toddlers and mothers pregnant. At first programs Posyandu carried out by the specific health to toddlers and pregnant mothers less is on good cooperation. It means, the community was not care with these programs, they are more inclined to silence at home rather than go to the PUSKESMAS join the programs Posyandu carried out by the health, but through socialization by Posyandu officers slowly but surely there has been a change in the community because of right now the were very excited about Posyandu programs. Keywords: participation, the community, posyandu program